Application of LC-MS/MS Coupled with Various Digestion Methods for the Identification of Porcine Gelatin Markers in Confectionery Matrices - Dewi, Kifayati Rosiyanti; Kusnandar, Feri; Yuliana, Nancy Dewi; Ismayati, Maya; Solihat, Nissa Nurfajrin; Riantana, Handy; Heryani, Heryani (Indonesian Journal of Halal Research, 2023)
Gelatin is a high-risk ingredient in terms of its halal status. Liquid chromatography combined with mass spectrometry (LC-MS/MS) was used to identify the source of gelatin based on marker peptides and proved to deliver higher reliability than other methods. However, the digestion method is essential before LC-MS/MS analysis. This research evaluated different digestion methods against selected porcine gelatin marker peptides and assessed LC-MS/MS sensitivity through adulteration experiments in various mixed matrices. The study involved three digestion methods (conventional, microwave, and ultrasound) before LC-MS/MS analysis to determine the most effective method for detecting marker peptide targets from porcine gelatin. The appropriate method was applied to isolate porcine gelatin peptides in the matrices of bovine gelatin and confectionery products (lozenges, marshmallows, and soft candy) at concentrations of 0.01, 0.1, and 1% (w/w). Relative detection limit values were determined. The results showed that conventional digestion treatment yielded a higher marker peptide detection rate than microwave and ultrasound digestion. Meanwhile, the detection limit of porcine gelatin in bovine gelatin ranged from 0.09 to 0.89%, depending on the marker peptide used, and could be significantly detected at a concentration of 1% in the confectionery product. The marker peptide TGQPGAVGPAGIR exhibited the highest stability, as it was detectable at the lowest concentration across all mixed matrices. The LC-MS/MS method has been proven to afford sensitive results and has the potential to serve as an alternative for detection of halal status.